Apoptotic Signaling Pathways in Glioblastoma and Therapeutic Implications. (12th November 2017) - Valdés-Rives, Silvia Anahi; Casique-Aguirre, Diana; Germán-Castelán, Liliana; Velasco-Velázquez, Marco A.; González-Arenas, Aliesha
Abstract : Glioblastoma multiforme (GBM) is the most hostile type of brain cancer. Its aggressiveness is due to increased invasion, migration, proliferation, angiogenesis, and a decreased apoptosis. In this review, we discuss the role of key regulators of apoptosis in GBM and glioblastoma stem cells. Given their importance in the etiology and pathogenesis of GBM, these signaling molecules may represent potential therapeutic targets.